Interrelationships among litter chemistry, plant species diversity, and litter decomposition in tropical stream environments: a review - Rabelo, Raiane S.; Sena, Guilherme; Gonçalves, José F. (Frontiers in Geochemistry, 2024)
Factors that may accelerate decomposition are important for ecosystem functioning since plant litter decomposition is essential for carbon and nutrient cycling, but it is a generally slow process, which can take weeks up to years. In this context, studies have demonstrated that the chemical characteristics of litter mixtures can accelerate decomposition through several mechanisms. Tropical riparian forests are known for their high diversity of tree species, which leads to a wide array of litter types in tropical streams, each with distinct chemical properties. This underscores the key role of litter chemistry in significantly influencing the litter breakdown rate within of these streams. Here, we explore the interplay among litter chemistry, plant species diversity, and litter decomposition in tropical streams. We highlight the importance of litter physical and chemical characteristics for decomposition, as well as of the preservation of the natural floristic composition of tropical riparian forests. In this sense, more attention must be paid to the influence that the environment and phylogeny may have on the phytochemical characteristics of riparian forest plant species in different tropic biomes, and how the insertion of different exotic species interferes with the decomposition process. Furthermore, we emphasize the need for additional research into the consequences of the loss of rare plant species with unique functional characteristics to decomposition in tropical ecosystems.